Pengaruh CG dan Risiko Bank terhadap Kinerja Intellectual Capital yang Dimediasi oleh Capital Structure - Ayu Sri Prasetyowati (STIE Widya Manggala, 2021)
This study aims to examine the effect of corporate governance and bank risk on intellectual capital performance by capital structure. Intellectual capital performance is very useful for the management, especially for managing his company. Intellectual capital performance is useful for management to make decisions about budget and investments. This research about intellectual capital performance is interesting to do because inconsistency of the results of previous research. This study use 135 banking companies. The banking companies used are listed on the Indonesia Stock Exchange for the period of 2017-2019. The method used to test the effect of each variable in this study is multiple regression linear. The results of this study prove that capital structure is able to mediate the effect of bank risk on intellectual capital performance. Capital structure can not mediate the effect of corporate governance on intellectual capital performance.